2008
DOI: 10.1111/j.1538-7836.2008.03089.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible biotinylated oligosaccharides: a new approach for a better management of anticoagulant therapy

Abstract: To cite this article: Savi P, Herault JP, Duchaussoy P, Millet L, Schaeffer P, Petitou M, Bono F, Herbert JM. Reversible biotinylated oligosaccharides:a new approach for a better management of anticoagulant therapy. J Thromb Haemost 2008; 6: 1697-706.Summary. Objective: In order to obtain a neutralizable antithrombotic, a chimeric molecule (SSR126517E) containing the sequence of a long-lasting antithrombin (AT)-dependent anti-factor Xa pentasaccharide, idraparinux, linked to a biotin molecule was synthesized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 26 publications
1
51
0
1
Order By: Relevance
“…Designed to be more specific for fXa than LMWH, AVE5026, an ultralow-molecular-weight heparin, mainly targets fXa 11 ; idrabiotaparinux, a synthetic pentasaccharide, 12 and otamixaban 13 selectively target fXa; and RB006, an anticoagulant RNA aptamer, 14 specifically targets factor IXa. All of the new parenteral agents have a rapid onset of action and produce a predictable anticoagulant effect, which, in the case of idrabiotaparinux and RB006, can be rapidly neutralized by intravenous administration of avidin, a biotin-binding protein, or RB007, a complementary aptamer, respectively.…”
Section: Potential Advantages Of New Anticoagulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Designed to be more specific for fXa than LMWH, AVE5026, an ultralow-molecular-weight heparin, mainly targets fXa 11 ; idrabiotaparinux, a synthetic pentasaccharide, 12 and otamixaban 13 selectively target fXa; and RB006, an anticoagulant RNA aptamer, 14 specifically targets factor IXa. All of the new parenteral agents have a rapid onset of action and produce a predictable anticoagulant effect, which, in the case of idrabiotaparinux and RB006, can be rapidly neutralized by intravenous administration of avidin, a biotin-binding protein, or RB007, a complementary aptamer, respectively.…”
Section: Potential Advantages Of New Anticoagulantsmentioning
confidence: 99%
“…12 Consequently, idrabiotaparinux is given subcutaneously on a once-weekly basis. The drug is excreted unchanged by the kidneys.…”
Section: Idrabiotaparinuxmentioning
confidence: 99%
“…Notably, avidin binding to EP217609 was found to cause a large loss in inhibitor potency (100-fold increase in K I for thrombin and 20-to 30-fold increase in the K D for antithrombin binding), contributing to an immediate neutralization of the drug's activity in addition to the indirect neutralization caused by avidin accelerating its clearance. 15,35 Phase 1 clinical studies in humans have indeed shown that administration of avidin triggers a rapid and irreversible neutralization of EP217609 without rebound effect. 18 The selectivity of EP217609 as a direct thrombin inhibitor largely derives from the extremely high affinity of the ␣-NAPAPlike moiety for thrombin (K I ϭ 30-40pM), which ranks among the highest-affinity direct thrombin inhibitors known.…”
Section: Discussionmentioning
confidence: 99%
“…It has a half-life of 130 h. 20 This permits once-weekly subcutaneous administration. The advantage of idrabiotaparinux over idraparinux is that it contains a biotin moiety which permits rapid reversal of anticoagulant action with intravenous avidin as the biotin-avidin complex terminates the drug action.…”
Section: New Orally Active Anticoagulants: Direct Factor Xa and Direcmentioning
confidence: 99%
“…The advantage of idrabiotaparinux over idraparinux is that it contains a biotin moiety which permits rapid reversal of anticoagulant action with intravenous avidin as the biotin-avidin complex terminates the drug action. 20 In a multicentre trial, patients with an objectively confirmed PE received 5-10 days treatment with enoxaparin before being randomly allocated to treatment with idrabiotaparinux given once weekly or to the group treated conventionally with warfarin for three to six months. 21 Outcome was assessed at 99 days after randomization.…”
Section: New Orally Active Anticoagulants: Direct Factor Xa and Direcmentioning
confidence: 99%